The Effect of Nozzle Type and Height on the Performance of the Ferto-15 Drone - M. Asqar Asqari Syafnur; Mahmud Achmad; Sitti Nur Faridah; Abdul Azis; Syahrial Sabaniah (Program Studi Teknik Pertanian Universitas Hasanuddin, 2026)
The efficiency of agricultural spraying drones heavily relies on hardware selection, such as nozzles, and operational parameters like flight height, which creates a trade-off between spray coverage and drift. This study aimed to analyze the effect of three nozzle types (flat fan, even fan, cone) and three flight heights (2 m, 2.5 m, and 3 m) on spray area, drift, efficiency, and uniformity (CU and DU) on the Ferto-15 drone. The research method employed a Completely Randomized Design (CRD) under static and dynamic test conditions, with spray volume data collected using catch cans. The results indicated that flight height was the most dominant factor; increasing height expanded the spray area but increased drift and decreased efficiency in dynamic tests. Nozzle type and its interaction with height had a pronounced effect under dynamic conditions, where the Flat-Fan nozzle consistently produced the most superior distribution uniformity (CU and DU). The main conclusion shows that the most optimal configuration was the use of the Flat-Fan nozzle at a 2-meter height, which provided the best balance between high deposition efficiency (95.89%), low drift (0.411 L), and superior uniformity (CU 89.89%). This finding demonstrates that achieving effective spraying performance depends on the synergistic combination of nozzle type and flight height.